Design and development of an electrospun polymeric transcatheter heart valve for tissue engineering - Guess, Rosslee Christie (Department of Human Biology, 2023)
The growing global burden of valvular heart disease (VHD) remains a significant challenge to overcome. Despite the advancements in heart valve replacements and the ground-breaking introduction of transcatheter valve technologies, current solutions offer suboptimal therapy as they either require lifelong anticoagulation or have limited durability. The ideal replacement valve should mimic the functionality of its native counterpart, comprise of viable living tissue, and offer lifelong durability, also for young patients. The central aims of this project were to design, manufacture, and evaluate two types of electrospun trileaflet transcatheter heart valve (THV) substitutes, one with non-degradable Pellethane® leaflets (PEL valves) and the other type using degradable DegraPol15® leaflets (DP valves). PEL and DP scaffolds were successfully electrospun after implementing a humidity control system and optimising input (ambient and processing) parameters; and were characterised for their morphological (fiber geometry and architecture), mechanical (static and dynamic), and hydraulic (wettability and permeability) properties. Six distinct valve manufacturing concepts (leaflet suturing, leaflet bonding, sandwich spinning, trileaflet preforming, inverted trileaflet preforming and submould assembly) were designed and prototyped for feasibility screening and selection. The selected concept was further employed to produce PEL and DP valves that were subsequently assessed for hydrodynamic function and durability by means of pulsatile flow analyses and accelerated fatigue testing. The fibres of DP scaffolds were approximately three times thicker than those in PEL scaffolds (5.2 ± 1.3 vs 1.8 ± 0.5 µm) with correspondingly larger pores (16.3 ± 4 vs 8.0 ± 1.7 µm). All scaffolds were essentially randomly oriented, and porosities averaged at 75 ± 5%. PEL scaffolds were approximately three times stronger than DP counterparts with slightly lower extensibility (550 vs 730%). From the six valve manufacturing concepts, the method involving the stitching of pre-cut leaflets onto the expandable stent (CoCr, 23 mm) after heat bonding an electrospun PEL skirt was selected. Four groups of valves, differing in average leaflet thickness (n = 2–4 per group), were produced for each material type. Under simulated aortic conditions, the PEL valves (N = 10) achieved remarkably high accelerated fatigue life of up to 260 million cycles (equivalent to 2.5 years), with a positive correlation between leaflet thickness and durability. The hydrodynamic parameters obtained for the PEL valves were well within ISO standards (EOA > 1.25 cm2 , mean pressure gradient < 10mmHg, and RF < 20% at a cardiac output of 5 l/min). In the current embodiments, DP valves (N=14) were not able to withstand aortic pressures but demonstrated good hydrodynamic function at nominal pulmonary pressures. Although much further study is required, the concepts described in this project contribute valuable insight into the manufacturing, performance, and durability of devices intended for transcatheter heart valve tissue engineering.